GROWTH PARAMETER ESTIMATES OF SEVEN SMALL INDIGENOUS FISH SPECIES FROM THE FOUR SELECTED FLOODPLAIN WETLANDS OF NORTH BIHAR, INDIA - RAUT, SHAILENDRA MOHAN; SINGH, JASPREET; KUMAR, MANOJ; SARMA, KAMAL; SINGH, INDU SEKHAR; GUPTA, NISHIKANT; RAMTEKE, KARANKUMAR KUMAR; SHARNAPPA, MOGALEKAR HAVAGIAPPA; SINGH, MUKESH KUMAR (Journal of the Inland Fisheries Society of India, 2024)
Morphometric study of length-weight relationship (LWR) and condition factors (K) of selected seven fish species from the floodplain wetland ecosystem of North Bihar. In the present investigation, 656 fishes (four families and seven species) out of 1426 fish samples were examined from floodplain wetlands of North Bihar, India.  The fish species were captured by local fishing gear (such as cast net, drag net, and bamboo traps) during June 2019 to January 2020. Salmostoma bacaila and Puntius shophore were the most abundant while Trichogaster fasciata and Esomus danricus constituted the least count in the fish catch. Length weight relationship’s b values varied from 0.72 to 3.24. The values of b indicated negative and positive allometric growth patterns, while the K values ranged between 0.80 and 1.28. Among the captured species Salmostoma bacaila, Esomus danricus, and Anabas testudineus recorded negative allometric growth (b